Advanced presentations by design : creating communication that drives action - Abela, Andrew V., 1965- (Pfeiffer, A Wiley Imprint, 2013)
Offering a new, exciting approach to the typically conventional practice for creating presentations, this new edition to a popular resource has compiled its material from more than 200 research studies in the fields of communication, marketing, psychology, multimedia, and law. The book demonstrates how to adapt a presentation to different audience personality preferences, what role the data should play and how much of it is necessary, how to turn data into a story, and how to design persuasive-yet-comprehensible visual layouts.